NEW TENDENCIES IN THE DEVELOPMENT OF THE FAMILY RITUALS OF THE DAGESTAN PEOPLES - Alimova, B M; Ibragimov, M -RA (History, Archeology and Ethnography of the Caucasus, 2016)
Basing on the field ethnographic materials, the data of focus-groups and blitz-surveys, the authors of the article trace transformations in the development of the modern family and the wedding rites of the Dagestan people. A relatively new type of wedding (wedding in the form of mawlid), called into being by a new stage of Islamization of the population, is fixed in Dagestan. The authors reveal the general trends in the development of the modern family and the family rites (including wedding ones) of the Dagestan people, involving transition from authoritarian and patriarchal principles to egalitarian (equitable) relationships, in which in the course of time young people will have greater autonomy and sideline the older generation.